Human Epidermal Growth Factor Receptor 2-positive Mucinous Carcinoma with Signet Ring Cell Differentiation, Which Showed Complete Response after Neoadjuvant Chemotherapy - Jang, Yunjeong; Cho, Eun Yoon; Cho, Soo Youn (Journal of breast cancer, 2019)
Mucinous carcinoma (MC) is a rare subtype of breast cancer, which is composed of tumor cells floating in the abundant extracellular mucin. This form of cancer is usually estrogen receptor/progesterone receptor positive and human epidermal growth factor receptor 2 (HER2) negative. Here, we present a case of HER2-positive MC with an unusual signet ring cell differentiation. It is very rare that a breast tumor consists entirely of signet ring cells. The tumor showed pathologic complete response (pCR) after neoadjuvant chemotherapy with trastuzumab and pertuzumab. pCR of HER2-positive MC has rarely been described in literature. It is important to consider the biological heterogeneity of MCs for effective management.